2020
DOI: 10.1016/j.soildyn.2019.105898
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of time of liquefaction using kinetic and strain energy

Abstract: The time of liquefaction triggering during a strong ground motion can have a large influence on the expected level of foundation and superstructure damage. To enable simple, yet accurate estimates of the triggering time, the build-up of pore pressure needs to be understood in terms of cumulative measures of ground motion intensity. This paper develops a theoretical framework and simple procedure to predict the build-up of excess pore pressure based on the principles of conservation of energy. The liquefaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Some of them only provide the factor of safety against liquefaction triggering, but others provide the whole pore pressure evolution during the earthquake duration including the time of liquefaction triggering. In this work, the strain energy-based model proposed by Millen et al (2020) was used, but other simplified models that provide the pore pressure time series could be used instead (see Seed et al 1975;Green et al 2000;Kokusho 2013;Rios et al 2019). In the method developed by Millen et al (2020), liquefaction resistance is measured in terms of normalized cumulative absolute strain energy (NCASE), which was shown to be insensitive to loading amplitude but sensitive to soil properties.…”
Section: Estimation Of Excess Pore Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Some of them only provide the factor of safety against liquefaction triggering, but others provide the whole pore pressure evolution during the earthquake duration including the time of liquefaction triggering. In this work, the strain energy-based model proposed by Millen et al (2020) was used, but other simplified models that provide the pore pressure time series could be used instead (see Seed et al 1975;Green et al 2000;Kokusho 2013;Rios et al 2019). In the method developed by Millen et al (2020), liquefaction resistance is measured in terms of normalized cumulative absolute strain energy (NCASE), which was shown to be insensitive to loading amplitude but sensitive to soil properties.…”
Section: Estimation Of Excess Pore Pressurementioning
confidence: 99%
“…In this work, the strain energy-based model proposed by Millen et al (2020) was used, but other simplified models that provide the pore pressure time series could be used instead (see Seed et al 1975;Green et al 2000;Kokusho 2013;Rios et al 2019). In the method developed by Millen et al (2020), liquefaction resistance is measured in terms of normalized cumulative absolute strain energy (NCASE), which was shown to be insensitive to loading amplitude but sensitive to soil properties. NCASE is defined as the cumulative change in absolute elastic strain energy divided by the initial vertical effective stress, σ 0 vo , [Eqs.…”
Section: Estimation Of Excess Pore Pressurementioning
confidence: 99%
“…The energy absorbed by the material may be evaluated based on the strain energy density, as used by Indraratna et al (2017) for monotonic shearing. Millen et al (2019) applied this concept to cyclic tests and suggested normalization by the effective confining stress σ'c, calling the obtained parameter NCASE (normalized accumulated absolute strain energy). The NCASE can be calculated with the following expression:…”
Section: Cyclic Testsmentioning
confidence: 99%
“…The contraction rate parameter ( h p0 ) was determined using the fitting expression, Eq. 3, from Millen et al (2020), where the target cyclic resistance ratio for 15 cycles ( CRR n15,target ) was determined using Eq. 4 from Boulanger and Idriss (2016), which is an empirical expression for the cyclic resistance for a magnitude 7.5 event.…”
Section: Influence Of Parameters On Ground Surface Shakingmentioning
confidence: 99%